A STUDY ON PRE-SERVICE TEACHERS’ REFLECTIVE PRACTICES IN IMPLEMENTING THE SCIENTIFIC APPROACH OF 2013 CURRICULUM - Purnamaningwulan, Rina Astuti (International Journal of Indonesian Education and Teaching (IJIET), 2019)
The pre-service teachers undertaking a teaching practice program (PPL – Program Pengalaman Lapangan) are demanded to implement the Scientific Approach, the underlying teaching practices in the 2013 curriculum (K13), in the schools where they conduct their teaching practice. The recent study aims to examine pre-service teachers’ problems in implementing Scientific Approach during a teaching practice program as reflected in their reflective journal entries. Also, this study seeks to find out how the reflective journal can help them improve their capability in implementing Scientific Approach when teaching English. The participants of this research were four pre-service teachers doing a teaching practice program in SMAN 8 Yogyakarta. This research employed a descriptive qualitative approach. The data were collected from participants’ reflective journal entries. From the study, it was found that participants encountered problems in implementing Scientific Approach in terms of maintaining student-centeredness in the teaching and learning process, engaging students’ participation, maintaining students’ focus, and applying the five learning stages based on Scientific Approach. Further, it was discovered that the reflective practice can help improve the pre-service teachers’ skills in implementing Scientific Approach in their English teaching practices.DOI: doi.org/10.24071/ijiet.2019.030203